Airborne food and aeroallergens levels in healthcare settings. An unaccounted but potentially relevant source of exposure? - Mariana da Silva Leal (2020)
Background: Exposure to airborne allergens of biological origin associates with the development and exacerbation of allergic asthma and rhinitis. Assessment of allergens exposure in healthcare facilities may contribute to monitor hygiene and survey specific allergens which may cause symptoms in sensitized subjects. Objective: To assess concentration of indoor and airborne food allergens across different healthcare settings. Methods: Dust was vacuumed from primary health care centers and emergency unit, day hospital, internal medicine ward, operating room and the outpatient clinic of a university central hospital. Samples were sieved, weighed, extracted and concentrations of Nbos d 5, Cor a 9, Gal d 2, Ara h 3, Ara h 6, Derp 1, Fel d 1, Can f 1, Bla g 2, Alt a 1 and Phl p 5 were determined using a multiplex array for allergens (MARIA(r)). Results: All airborne food and aeroallergens were found at least in one sampled area, except for Alt a 1. All levels of Derp 1 and almost all levels of Fel d 1 were above the threshold for the development of asthma symptoms, ranging from 13.0 g/g to 971.0 g/g and from 7.0 g/g to 4618.8 g/g, respectively. The emergency unit revealed the higher levels of food allergens, namely Nbos d 5 (16034.0 g/g) and Cor a 9 (10649.5 g/g). Conclusions: With the exception of the operating room, exposure levels across different healthcare settings were above the threshold for the development of allergic symptoms in mite, cat or dog sensitized subjects.